Gel electrolyte for iron-nickel battery as well as preparation method and application of gel electrolyte
The gel electrolyte for iron-nickel batteries addresses issues of energy density and leakage by forming stable ion channels, improving conductivity and cycle stability, and reducing corrosion, thus enhancing their performance in large-scale energy storage.
Patent Information
- Application Number
- CN202411574531.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-03
AI Technical Summary
Iron-nickel batteries face issues such as insufficient energy density, limited cyclability, hydrogen precipitation leading to internal pressure buildup, and poor rate performance, which can cause leakage and reduce their effectiveness in large-scale energy storage applications.
A gel electrolyte composed of aqueous electrolyte, polyvinyl alcohol, potassium polyacrylate, and electrolyte salts or additives like lithium sulfate, polyvinyl pyrrolidone, diammonium hydrogen phosphate, calcium lignin sulfonate, or chitosan, which forms a stable ion channel network enhancing conductivity and reducing leakage risks.
The gel electrolyte improves ion transport efficiency, increases discharge specific capacity, stabilizes cycle performance, and enhances energy density while being environmentally friendly, with a longer service life and reduced corrosion.
Smart Images

Figure CN119253089A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemistry, and in particular relates to a gel electrolyte for an iron-nickel battery and a preparation method and application thereof. Background Art
[0002] The iron-nickel battery is a rechargeable battery invented by Thomas Edison. Iron is abundant and widely distributed in the earth's crust, and the negative electrode material is relatively easy to obtain and low in cost, making it suitable for large-scale energy storage. Iron-nickel batteries are mainly used for long-term, medium-current use. Their operating voltage is 1.2V. They are durable and can withstand a certain degree of use accidents (including overcharging, over-discharging, short circuit, overheating), and can still maintain a long life after such damage. The use of more environmentally friendly electrolytes can also effectively prevent safety issues of organic electrolytes during the charging and discharging process. Although iron-nickel batteries have broad application prospects in the future, the problems of the material itself still exist and have caused many problems, including insufficient energy density, limited cyclability, large amounts of hydrogen precipitation, poor rate performance, and in large-scale energy storage devices, the long-term accumulation of hydrogen increases the internal pressure of the battery, causing the battery to leak electrolyte.
[0003] In my country, the development of iron-nickel batteries started later than that of foreign countries, but it has also been vigorously developed, and has developed rapidly in the later period. Since the 1980s, the research on iron-nickel batteries has been mainly carried out in some universities and enterprises. Lin Dongfeng and others from Nankai University have been devoted to the research of iron-nickel secondary batteries, and have achieved certain results, successively solving problems such as low charging efficiency and poor rate discharge performance. Xiang Min and others from Zhengzhou Institute of Light Industry and Chemical Engineering reported on the research status of iron electrodes, focusing on summarizing the problems existing in iron electrodes, and summarizing methods to solve problems such as passivation and self-discharge of iron electrodes. Around 2011, Li Qingsong and others found through research that the use of nickel foam as a current collector can increase the specific capacity of the electrode. The higher the solubility of the electrolyte, the greater the expansion coefficient of the iron negative electrode. It was also found that adding NO3 to the electrolyte - In 2012, Fei Wei and others jointly developed an ultra-fast charging iron-nickel battery, which can obtain 120Wh kg in just 2 minutes of charging and 30 seconds of discharge. -1Specific energy. When Na2S was added to the electrolyte of You Wanxiang of Harbin Institute of Technology, the discharge capacity reached 560mA·h / g at a discharge rate of 0.1C, and the high and low temperature performance of the battery was improved. The discharge capacity was 550mA·h / g at 5°C and 650mA·h / g at 40°C, and it would not cause self-discharge of the battery. In China, semi-solid gel polymer electrolytes are relatively widely used in lithium-ion batteries. Zhao et al. used dimethyl methylphosphonate (DMMP) as a functional flame retardant and plasticizer for polyvinylidene fluoride (PVDF) matrix and developed a new type of non-flammable PVDF-DMMP GPEs for lithium-ion batteries. This DMMP not only greatly enhanced the flame retardancy of PVDF-DMMP GPEs, but also effectively improved the dissociation efficiency of lithium salts and the rapid transmission of lithium ions. Li et al. used a solution casting method to cast polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) containing β-cyclodextrin (β-CD) additive on a pretreated polyethylene (PE) substrate to prepare a PVDF-HFP / β-CD@PE composite gel polymer electrolyte. The results showed that when the β-CD addition amount was 5.0wt%, the ionic conductivity, lithium ion transference number and electrochemical stability window of the obtained composite gel polymer electrolyte were 4.851×10 -4 S / cm, 0.77, 5.1V (vs Li+ / Li), and the discharge capacity of the assembled Li||LiFePO4 battery is 168.1mAh g -1 , and remained stable after 150 cycles. The advantages of applying gel electrolyte to iron-nickel batteries are even more obvious. It can effectively solve the problem of electrolyte volatilization and leakage in large-scale energy storage equipment. It is of great significance to carry out research on polymer electrolytes suitable for iron-nickel batteries.
[0004] Gel electrolytes have attracted much attention in the new energy industry. Compared with traditional liquid electrolytes, gel systems can fix electrolytes in the electrode apertures, thereby avoiding problems such as leakage and volatilization of liquid electrolytes. The plates will not corrode, and the service life is longer than that of traditional liquid electrolyte batteries. Gel electrolytes can form a large number of ion channels in the electrode apertures, with a high degree of ionization, which makes the gel electrolyte have a higher conductivity and the energy density of the battery can be greatly improved. Gel electrolytes do not contain pollutants such as heavy metals, have a high recovery and reuse rate, and are more environmentally friendly. Summary of the invention
[0005] In view of the technical defects existing in traditional liquid electrolytes, the purpose of the present invention is to provide a method for preparing a gel electrolyte for iron-nickel batteries. The gel electrolyte overcomes some technical difficulties, has the advantages of low flow, uniform distribution of active substances, and reduced risks such as leakage and volatilization of electrolytes. At the same time, the interaction force between electrolyte molecules is greater than the interaction between water molecules, so it can effectively reduce the problem of electrolyte creeping out caused by gas production.
[0006] A gel electrolyte for an iron-nickel battery, the gel electrolyte comprising the following components:
[0007] Aqueous electrolyte: 80-90wt%;
[0008] Polyvinyl alcohol: 8-10wt%;
[0009] Potassium polyacrylate: 1-4wt%;
[0010] and electrolyte salts or additives;
[0011] The electrolyte salt is 0.2-1wt% lithium sulfate, and the additive is one of 1-4wt% polyvinyl pyrrolidone, 0.2-1wt% diammonium hydrogen phosphate, 0.2-0.8wt% calcium lignin sulfonate, and 1-4wt% chitosan;
[0012] The aqueous electrolyte comprises the following components: KOH: 20-50 wt%, LiOH: 1-2 wt%, and the balance is water.
[0013] The preparation method of the gel electrolyte for iron-nickel battery specifically comprises the following steps:
[0014] Step S1: weighing raw materials according to the material components to prepare an aqueous electrolyte;
[0015] Step S2: dissolving polyvinyl alcohol and potassium polyacrylate in the aqueous electrolyte obtained in step S1 in sequence to obtain a mixed solution;
[0016] Step S3: adding electrolyte salt or additives to the mixed solution obtained in step S2, and mixing to obtain a gel electrolyte for an iron-nickel battery.
[0017] The step S1 specifically includes the following steps:
[0018] Step S11: weighing raw materials according to the mass percentage of each substance component of the aqueous electrolyte;
[0019] Step S12: adding the raw material obtained in step S11 into water in multiple portions, and stirring to obtain a clear solution;
[0020] Step S13: The solution obtained in step S12 is sealed to avoid oxidation, and is allowed to stand and cool at room temperature until the solution temperature drops to room temperature. The obtained solution is an aqueous electrolyte.
[0021] The step S2 specifically includes the following steps:
[0022] Step S21: heating the aqueous electrolyte for standby use;
[0023] Step S22: weighing polyvinyl alcohol and potassium polyacrylate according to a ratio, and then sequentially adding the polyvinyl alcohol and potassium polyacrylate into the aqueous electrolyte, mixing evenly, and stirring;
[0024] Step S23: Continue heating after mixing and continue stirring until the mixture is fully mixed.
[0025] In the step S23, the temperature is heated to 80-95°C and the stirring time is 0.5-1h.
[0026] The step S3 specifically includes the following steps:
[0027] Step S31: adding a certain amount of lithium sulfate or polyvinyl pyrrolidone to the prepared electrolyte, and stirring until the mixture is uniformly mixed;
[0028] Step S32: Seal the uniformly mixed electrolyte to avoid oxidation, and let it stand to obtain a gel electrolyte.
[0029] In the step S31, manual stirring is used in the stirring process.
[0030] In the step S32, the static time is 12 to 24 hours.
[0031] The application of the gel electrolyte for iron-nickel batteries is specifically to prepare iron-nickel batteries, comprising the following steps:
[0032] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0033] The principle of the gel electrolyte for iron-nickel battery prepared by the present invention is as follows:
[0034] 1. The gel electrolyte prepared by the present invention uses polyvinyl alcohol and potassium polyacrylate as the electrolyte base for two reasons: first, the polymer itself is a high molecular substance, which can undergo a cross-linking reaction and has good mechanical properties and swelling properties; second, the polymer can accelerate the transport rate of ions through complex ionic compounds, while maintaining the original mechanical stability, it has better conductivity, interfacial tension and interfacial compatibility.
[0035] 2. In step S1 of the present invention, the alkaline substance must be added to the stirred solution in multiple times. If it is added all at once, a large amount of heat will be generated, causing the solution to boil and the electrolyte to evaporate, resulting in an inaccurate electrolyte ratio.
[0036] 3. In alkaline polymer electrolytes, the PVA-KOH system has good mechanical properties, but the maximum conductivity at room temperature is only 2.01×10 -3 Scm -1 , while the maximum conductivity of the PAAK system at room temperature can be 0.288Scm -1 , but its mechanical properties are poor. Therefore, in the present invention, two polymer electrolytes are mixed and used, and polyvinyl alcohol and potassium polyacrylate are non-toxic, non-corrosive, soluble in water, easily soluble in alkaline solutions and can exist stably. In addition, potassium polyacrylate has a certain water retention capacity, and the viscosity changes little after being dissolved in alkaline electrolyte for a long time.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. Electrolyte salts are generally used as additives to improve the performance of gel polymer electrolytes. The present invention uses lithium sulfate, a salt with a strong solvation effect, to effectively improve the ion transport efficiency, greatly increase the discharge specific capacity, and make the cycle performance more stable.
[0039] 2. Compared with traditional liquid electrolytes, the gel system provided by the present invention can fix the electrolyte in the electrode pores, thereby avoiding problems such as leakage and volatilization of the liquid electrolyte. The electrode plate will not corrode and the service life is longer than that of traditional liquid electrolyte batteries.
[0040] 3. The gel electrolyte provided by the present invention can form a large number of ion channels in the electrode pores, and the degree of ionization is relatively high, so that the gel electrolyte has a higher conductivity, and the energy density of the battery can also be greatly improved. In addition, the gel electrolyte does not contain pollutants such as heavy metals, has a high recovery and reuse rate, and is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The specific capacity discharge diagram of the gel electrolyte prepared in Comparative Example 1 of the present invention used in an iron-nickel battery;
[0042] Figure 2 The specific capacity discharge diagram of the aqueous electrolyte prepared in Comparative Example 2 of the present invention for use in an iron-nickel battery;
[0043] Figure 3 Specific capacity discharge diagram of the gel electrolyte prepared in Examples 1, 2, 5 of the present invention and Comparative Example 1 used in an iron-nickel battery. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. The following are embodiments to help those skilled in the art further understand the present invention, but do not limit the present invention in any form. All technologies realized based on the above-mentioned content of the present invention belong to the protection scope of the present invention.
[0045] Example 1
[0046] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0047] Step S1: 44 wt% of KOH, 1.9 wt% of LiOH and deionized water are weighed according to the mass ratio, and the total amount of the three is 100 wt%.
[0048] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0049] Step S2: using alkaline aqueous electrolyte to prepare gel electrolyte, wherein the components of the gel electrolyte are, by mass fraction, 10 wt % of polyvinyl alcohol, 3.3 wt % of potassium polyacrylate, 3.3 wt % of polyvinyl pyrrolidone, and the remainder is alkaline aqueous electrolyte, and the total amount of the four is 100 wt %.
[0050] The preparation process of gel electrolyte is as follows: place the alkaline aqueous electrolyte in a magnetic stirrer for stirring, weigh 10wt% of polyvinyl alcohol, slowly add it to the alkaline electrolyte, heat the electrolyte after all are mixed, this process will form an electrolyte with lower viscosity, take out the rotor, stir with a glass rod, heat to about 90°C, and the polyvinyl alcohol is completely dissolved; weigh 3.3wt% of potassium polyacrylate, slowly add it to the electrolyte, stir with a glass rod while adding, the stirring time is 0.5h, mix thoroughly and evenly, and obtain a mixed solution.
[0051] Step S3: Add 3.3 wt % polyvinyl pyrrolidone to the mixed solution obtained in step S2, stir with a glass rod while adding, and seal with plastic wrap and let stand for 24 hours after fully mixing, to obtain an alkaline gel electrolyte.
[0052] The alkaline gel electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0053] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0054] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0055] Example 2
[0056] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0057] Step S1: 44 wt% of KOH, 1.9 wt% of LiOH and deionized water are weighed according to the mass ratio, and the total amount of the three is 100 wt%.
[0058] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0059] Step S2: using alkaline aqueous electrolyte to prepare gel electrolyte, wherein the components of the gel electrolyte are, by mass fraction, 10wt% polyvinyl alcohol, 3.3wt% potassium polyacrylate, 1wt% lithium sulfate, and the remainder is alkaline aqueous electrolyte, and the total amount of the four is 100wt%.
[0060] The preparation process of gel electrolyte is as follows: place the alkaline aqueous electrolyte in a magnetic stirrer for stirring, weigh 10wt% of polyvinyl alcohol, slowly add it to the alkaline electrolyte, heat the electrolyte after all are mixed, this process will form an electrolyte with lower viscosity, take out the rotor, stir with a glass rod, heat to about 90°C, and the polyvinyl alcohol is completely dissolved; weigh 3.3wt% of potassium polyacrylate, slowly add it to the electrolyte, stir with a glass rod while adding, the stirring time is 0.5h, mix thoroughly and evenly, and obtain a mixed solution.
[0061] Step S3: Add 1 wt % lithium sulfate to the mixed solution obtained in step S2, stir with a glass rod, mix thoroughly and evenly, seal with plastic wrap and let stand for 24 hours to obtain an alkaline gel electrolyte.
[0062] The alkaline gel electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0063] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0064] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0065] Example 3
[0066] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0067] Step S1: 44 wt% of KOH, 1.9 wt% of LiOH and deionized water are weighed according to the mass ratio, and the total amount of the three is 100 wt%.
[0068] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0069] Step S2: using an alkaline aqueous electrolyte to prepare a gel electrolyte, wherein the components of the gel electrolyte are, by mass fraction, 10 wt % of polyvinyl alcohol, 3.3 wt % of potassium polyacrylate, 1 wt % of ammonium dihydrogen phosphate, and the remainder is an alkaline aqueous electrolyte, and the total amount of the four is 100 wt %.
[0070] The preparation process of gel electrolyte is as follows: place the alkaline aqueous electrolyte in a magnetic stirrer for stirring, weigh 10wt% of polyvinyl alcohol, slowly add it to the alkaline electrolyte, heat the electrolyte after all are mixed, this process will form an electrolyte with lower viscosity, take out the rotor, stir with a glass rod, heat to about 90°C, and the polyvinyl alcohol is completely dissolved; weigh 3.3wt% of potassium polyacrylate, slowly add it to the electrolyte, stir with a glass rod while adding, the stirring time is 0.5h, mix thoroughly and evenly, and obtain a mixed solution.
[0071] Step S3: Add 1 wt % of ammonium dihydrogen phosphate to the mixed solution obtained in step S2, stir with a glass rod while adding, and seal with plastic wrap and let stand for 24 hours after fully mixing, to obtain an alkaline gel electrolyte.
[0072] The alkaline gel electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0073] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0074] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0075] Example 4
[0076] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0077] Step S1: 44 wt% of KOH, 1.9 wt% of LiOH and deionized water are weighed according to the mass ratio, and the total amount of the three is 100 wt%.
[0078] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0079] Step S2: using alkaline aqueous electrolyte to prepare gel electrolyte, wherein the components of the gel electrolyte are, by mass fraction, 10 wt % of polyvinyl alcohol, 3.5 wt % of potassium polyacrylate, 0.8 wt % of calcium lignin sulfonate, and the remainder is alkaline aqueous electrolyte, and the total amount of the four is 100 wt %.
[0080] The preparation process of gel electrolyte is as follows: place the alkaline aqueous electrolyte in a magnetic stirrer for stirring, weigh 10wt% of polyvinyl alcohol, slowly add it to the alkaline electrolyte, heat the electrolyte after all are mixed, this process will form an electrolyte with lower viscosity, take out the rotor, stir with a glass rod, heat to about 90°C, and the polyvinyl alcohol is completely dissolved; weigh 3.5wt% of potassium polyacrylate, slowly add it to the electrolyte, stir with a glass rod while adding, the stirring time is 0.5h, mix thoroughly and evenly, and obtain a mixed solution.
[0081] Step S3: Add 0.8 wt % of calcium lignin sulfonate to the mixed solution obtained in step S2, stir with a glass rod while adding, and seal with plastic wrap and let stand for 24 hours after fully mixing, to obtain an alkaline gel electrolyte.
[0082] The alkaline gel electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0083] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0084] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0085] Example 5
[0086] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0087] Step S1: 44 wt% of KOH, 1.9 wt% of LiOH and deionized water are weighed according to the mass ratio, and the total amount of the three is 100 wt%.
[0088] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0089] Step S2: using alkaline aqueous electrolyte to prepare gel electrolyte, wherein the components of the gel electrolyte are, by mass fraction, 10 wt % of polyvinyl alcohol, 3.3 wt % of potassium polyacrylate, 3.3 wt % of chitosan, and the remainder is alkaline aqueous electrolyte, and the total amount of the four is 100 wt %.
[0090] The preparation process of gel electrolyte is as follows: place the alkaline aqueous electrolyte in a magnetic stirrer for stirring, weigh 10wt% of polyvinyl alcohol, slowly add it to the alkaline electrolyte, heat the electrolyte after all are mixed, this process will form an electrolyte with lower viscosity, take out the rotor, stir with a glass rod, heat to about 90°C, and the polyvinyl alcohol is completely dissolved; weigh 3.3wt% of potassium polyacrylate, slowly add it to the electrolyte, stir with a glass rod while adding, the stirring time is 0.5h, mix thoroughly and evenly, and obtain a mixed solution.
[0091] Step S3: Add 3.3 wt % chitosan to the mixed solution obtained in step S2, stir with a glass rod, mix thoroughly and evenly, seal with plastic wrap and let stand for 24 hours to obtain an alkaline gel electrolyte.
[0092] The alkaline gel electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0093] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0094] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0095] Comparative Example 1
[0096] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0097] Step S1: 44 wt% of KOH, 1.9 wt% of LiOH and deionized water are weighed according to the mass ratio, and the total amount of the three is 100 wt%.
[0098] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0099] Step S2: using the alkaline aqueous electrolyte to prepare a gel electrolyte, wherein the components of the gel electrolyte are, by mass fraction, 10 wt % of polyvinyl alcohol, 3.3 wt % of potassium polyacrylate, and the remainder of the alkaline aqueous electrolyte, and the total amount of the three is 100 wt %.
[0100] The preparation process of the gel electrolyte is as follows: place the alkaline aqueous electrolyte in a magnetic stirrer for stirring, weigh 10wt% of polyvinyl alcohol, slowly add it to the alkaline electrolyte, and heat the electrolyte after all are mixed. This process will form an electrolyte with lower viscosity. Take out the rotor, stir with a glass rod, heat to about 90°C, and the polyvinyl alcohol is completely dissolved; weigh 3.3wt% of potassium polyacrylate, slowly add it to the electrolyte, stir with a glass rod while adding, the stirring time is 0.5h, after fully mixing, seal with plastic wrap and let stand for 24h to obtain an alkaline gel electrolyte.
[0101] The alkaline gel electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0102] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
[0103] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0104] The specific capacity discharge diagram of the iron-nickel battery obtained in Comparative Example 1 is as follows: Figure 1 As shown, the specific capacity discharge diagrams of the iron-nickel batteries obtained in Examples 1, 2, 5 and Comparative Example 1 are shown in Figure 3 shown.
[0105] Comparative Example 2
[0106] A method for preparing a gel electrolyte for an iron-nickel battery comprises the following steps:
[0107] 44 wt% of KOH, 1.9 wt% of LiOH and deionized water were weighed according to the mass ratio, and the total amount of the three was 100 wt%.
[0108] The preparation process of the aqueous electrolyte is as follows: KOH and LiOH are added to deionized water in small amounts and multiple times, and stirred at the same time. A large amount of heat will be released during the dissolution process. After all the substances are dissolved, a clear solution is obtained. The clear solution is sealed with plastic wrap to avoid oxidation, and left to stand at room temperature for 2 hours to cool to room temperature to obtain an alkaline aqueous electrolyte.
[0109] The alkaline aqueous electrolyte prepared above is used to prepare an iron-nickel battery, comprising the following steps:
[0110] The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, the slurry is evenly applied on the nickel foam, and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared alkaline aqueous electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the positive and negative electrode sheets are assembled together and put into a closed bag, and the alkaline aqueous electrolyte is added to obtain an iron-nickel battery.
[0111] The prepared battery was placed at rest for 12 hours and then connected to the Blue Power CT2001A battery testing system for activation. After the battery was activated, the constant current charge and discharge cycle test was started. The charge and discharge program was set as follows: charge at 0.2C current for 5 hours, place at rest for 15 minutes, discharge at 0.2C current, terminate discharge after the voltage reaches 0.7V, and place at rest for 15 minutes as a charge and discharge program cycle. The number of cycles was set to 30, and the changes in relevant parameters such as charge and discharge battery voltage and discharge capacity were analyzed.
[0112] The specific capacity discharge diagram of the iron-nickel battery obtained in Comparative Example 2 is as follows: Figure 2 shown.
Claims
1. A gel electrolyte for an iron-nickel battery, characterized in that: The gel electrolyte comprises the following components: Aqueous electrolyte: 80-90wt%; Polyvinyl alcohol: 8-10wt%; Potassium polyacrylate: 1-4wt%; and electrolyte salts or additives; The electrolyte salt is 0.2-1wt% lithium sulfate, and the additive is one of 1-4wt% polyvinyl pyrrolidone, 0.2-1wt% diammonium hydrogen phosphate, 0.2-0.8wt% calcium lignin sulfonate, and 1-4wt% chitosan.
2. The gel electrolyte for an iron-nickel battery according to claim 1, characterized in that: The aqueous electrolyte comprises the following components: KOH: 20-50 wt%, LiOH: 1-2 wt%, and the balance is water.
3. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 1, characterized in that: The specific steps include: Step S1: weighing raw materials according to the material components to prepare an aqueous electrolyte; Step S2: dissolving polyvinyl alcohol and potassium polyacrylate in the aqueous electrolyte obtained in step S1 in sequence to obtain a mixed solution; Step S3: adding electrolyte salt or additives to the mixed solution obtained in step S2, and mixing to obtain a gel electrolyte for an iron-nickel battery.
4. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 3, characterized in that: The step S1 specifically includes the following steps: Step S11: weighing raw materials according to the mass percentage of each substance component of the aqueous electrolyte; Step S12: adding the raw material obtained in step S11 into water in multiple portions, and stirring to obtain a clear solution; Step S13: The solution obtained in step S12 is sealed to avoid oxidation, and is allowed to stand and cool at room temperature until the solution temperature drops to room temperature. The obtained solution is an aqueous electrolyte.
5. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 3, characterized in that: The step S2 specifically includes the following steps: Step S21: heating the aqueous electrolyte for standby use; Step S22: weighing polyvinyl alcohol and potassium polyacrylate according to a ratio, and then sequentially adding the polyvinyl alcohol and potassium polyacrylate into the aqueous electrolyte, mixing evenly, and stirring; Step S23: Continue heating after mixing and continue stirring until the mixture is fully mixed.
6. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 4, characterized in that: In the step S23, the temperature is heated to 80-95°C and the stirring time is 0.5-1h.
7. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 2, characterized in that: The step S3 specifically includes the following steps: Step S31: adding a certain amount of lithium sulfate or polyvinyl pyrrolidone to the prepared electrolyte, and stirring until the mixture is uniformly mixed; Step S32: Seal the uniformly mixed electrolyte to avoid oxidation, and let it stand to obtain a gel electrolyte.
8. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 2, characterized in that: In the step S31, manual stirring is used in the stirring process.
9. The method for preparing a gel electrolyte for an iron-nickel battery according to claim 2, characterized in that: In the step S32, the static time is 12 to 24 hours.
10. The use of a gel electrolyte for an iron-nickel battery according to claim 1, characterized in that: Specifically, the preparation of an iron-nickel battery includes the following steps: The positive and negative electrode raw materials are respectively stirred evenly to form a viscous electrode slurry, and the slurry is evenly applied on the nickel foam and reserved as the positive and negative electrode ears, and the positive and negative electrode sheets are obtained after drying; the prepared gel electrolyte is evenly applied on the positive and negative electrode sheets rolled by an electric roller machine, and the positive and negative electrode sheets are respectively wrapped with diaphragms, and then the gel electrolyte is evenly applied on the positive and negative electrode surfaces with diaphragms according to the size of the positive and negative electrode sheets, and the positive and negative electrode sheets are assembled together with tape and put into a closed bag, and the gel electrolyte is added to obtain an iron-nickel battery.
